PENGARUH PEMBELAJARAN KONSTRUKTIVISME TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS IV SD - Juliani Juliani; Ida Ermiana; Awal Nur Kholifatur Rosyidah (Renjana Pendidikan Dasar, 2022)
Problem solving ability must be possessed by students as a basic ability in learning mathematics, to practice problem solving skills, a learning process that facilitates the achievement of students' mathematical problem solving skills is needed. The purpose of this study was to determine the effect of constructivism learning on the mathematical problem solving ability of fourth grade students at SDN 1 Labuan Lombok. This type of research is an experimental study with a pre-experimental design type one group pretest posttest. The sample of this research is the fourth grade students of SDN 1 Labuan Lombok, totaling 31 people. Data collection methods are observation, test, and documentation. The validity test uses an expert test which states that the instrument is feasible to collect data. The results of the normality test of the data with a significance level of 5% obtained a significance value of 0.200 > 0.05 for the pretest data and 0.160 > 0.05 for the posttest, which means that the data is normally distributed, the homogeneity test results obtained a significance value of 0.875 > 0.05 which means that the data homogeneous. After knowing that the data is normally distributed and homogeneous, then hypothesis testing is carried out using a paired simple t test with a significance value of 0.000 <0.05, this means that H_0 is rejected and H_a is accepted. This means that there are differences in students' mathematical problem solving abilities before and after using constructivism learning. The magnitude of the influence of constructivism learning is calculated by using the N Gain Test, it is obtained a value of 0.31 is classified as moderate so it can be concluded that there is an effect of constructivism learning on the mathematical problem solving ability of fourth grade students at SDN 1 Labuan Lombok.